Triboelectric nanogenerator and its manufacturing method
Patent Information
- Application Number
- KR1020240164248
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-11-16
- Filing Date
- 2024-11-18
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2044-11-18
Smart Images

Figure 112024126583162-PAT00005_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a triboelectric nanogenerator and a method for manufacturing the same. Background Technology
[0002] The demand for portable sustainable power sources is increasing due to advancements in portable devices, wireless sensor networks, wearable electronics, and the Internet of Things (IoT). Energy demand solutions other than renewable energy sources are causing major environmental and ecological problems, including global warming. Therefore, there is a need to develop clean and eco-friendly energy harvesting and storage technologies.
[0003] Various strategies have been employed to harvest mechanical energy based on triboelectric effects, piezoelectric effects, electrostatic generation, or electromagnetic induction, and these strategies have been used to convert mechanical motion into sustainable electrical energy. Furthermore, various sustainable energy harvesters have been developed for self-driven sensing applications. In particular, triboelectric nanogenerators (TENGs) have garnered significant interest due to their low weight, excellent electrical output performance, cost-effectiveness, ease of fabrication, suitability for mass production, and ease of handling.
[0004] TENGs can convert mechanical motion into sustainable electrical energy by combining electrostatic induction and triboelectricity. TENG devices generate voltage and current when two frictional materials of opposite polarity come into contact. However, it is difficult to obtain high output current from TENG devices. Furthermore, the triboelectric performance, effective contact area, and dielectric properties achieved using pure polymers, metals, and metal oxide materials fall short of the levels required to power portable electronic devices and for real-time applications.
[0005] Various surface modification approaches, such as inductively coupled plasma etching, lithography, reactive ion etching, screen printing, thermal imprint lithography, 3D printing, and photolithography, have been used to improve the surface roughness and electrical performance of TENGs. However, these approaches are costly, complex, difficult to tune pattern features, and require careful operation.
[0006] On the other hand, membranes or layers of TENGs can be fabricated using microfabrication, sputtering, electrospinning, and reactive ion etching techniques. In particular, electrospinning provides an easy and versatile means of producing polymer nanofibers with appropriate surface roughness, a high volume-to-surface ratio, high porosity, mechanical strength, surface area, and excellent flexibility. Due to these characteristics, electrospun polymer nanofiber membranes are suitable candidates for improving the surface charge density of triboelectric polymer materials and thereby increasing electrical output characteristics.
[0007] To improve the electrical output of TENGs, it is essential to use tribomaterials that enhance triboelectric properties. PVDF and its polymers are frequently used to design the triboelectric cathode layer of TENGs. Improving the β phase of PVDF can also improve the overall electrical behavior of TENGs. However, to enhance the charge transfer characteristics of PVDF and produce high-performance PVDF-based TENG devices, it is important to incorporate dielectrics and electroactive fillers.
[0008] Various functional nanocomposite fillers, such as graphene quantum dots, carbon nanotubes, and silver nanowires, have been incorporated to enhance the triboelectric behavior of PVDF and its copolymers. Recently, 2D Ti3C2Tx-based MXene materials have garnered attention in the field of energy harvesting and storage. Excellent fillers are required to improve the triboelectric and dielectric properties of polymeric materials that possess excellent conductivity, diverse surface chemistry, abundant fluorine groups, high carrier charge mobility, high electronegativity, excellent mechanical properties, and terminal functional groups. In this regard, MXene can modify the charge transfer characteristics of PVDF and improve the triboelectric properties of PVDF-MXene nanofibers.
[0009] While negatively charged triboelectric materials are widely used, positively charged triboelectric materials are difficult to obtain, making selection difficult. Through experimental and theoretical studies, it is known that the electrical output characteristics of TENGs are determined by the polarization phenomenon induced by electrostatic surface charges induced by triboelectricity. PAN is an amorphous vinyl polymer containing repeating cyano units, and the dipole moment of a PAN unit is approximately 3.5 Debye. On the other hand, PAN is not known for use as a triboelectric material because it has low electrical output characteristics and poor triboelectric effects.
[0010] Therefore, to improve electrical properties, the surface roughness of PAN fibers must be increased. However, an effective surface contact area can be achieved by creating micro / nano and porous features in triboelectric materials or by incorporating porous materials. Over the past few years, porous materials such as zeolite imidazole frameworks (ZIFs) have been widely used in energy harvesting applications.
[0011] Meanwhile, ZIF is a crystalline porous material formed by the self-assembly of organic ligands and metal clusters or metal ions through the formation of coordination bonds. Generally, ZIF bridge ligands can be utilized as energy-collecting antennas that transfer charge from organic linkers to metal ions at connecting nodes. Furthermore, the crystal structure of ZIF is primarily influenced by metal ions with random geometric shapes and various organic ligands coordinated at random positions.
[0012] In the present invention, the surface area of PAN and PVDF nanofibers was increased using electrospinning. Furthermore, both polymers possess abundant polar C≡N and fluorine groups, which can enhance triboelectricity and potentially increase the electrical output of TENGs. The following strategy was utilized to create roughness in the PAN nanofibers. The PAN nanofibers formed a fiber film resembling a pearl necklace and were decorated with ZIF-67 nanocrystals to provide greater roughness.
[0013] PAN nanofibers were immersed in a ZIF-67 solution for various durations (1, 5, 10, and 24 hours) to obtain films with different surface roughness. ZIF-67@PAN nanofibers act as triboelectric positive films with higher surface roughness, which can induce high performance in the ZP-TENG device. Additionally, various cathodic PVDF@MXene nanofibers were electrospun by adding MXene to a PVDF solution at various concentrations, thereby improving the triboelectric properties of the ZP-TENG device. The surface charge density and dielectric properties of the PVDF@MXene nanofibers were evaluated.
[0014] The inventors confirmed that the optimized ZP-TENG device (ZIF-67@PAN-10h) exhibits higher electrical performance than previously reported studies. The optimized device efficiently powers LEDs and LCDs of portable timer clocks and is used as a self-contained power sensor. Furthermore, the present invention was completed by systematically investigating real-time and practical applications of the ZP-TENG device. Prior art literature
[0015] Korean Registered Patent KR 10-1973999 The problem to be solved
[0016] The object of the present invention is to provide a triboelectric nanogenerator comprising: a first electrode formed on a first substrate; a second electrode formed on a second substrate and disposed opposite to the first electrode; a negative friction layer formed on the first electrode; and a positive friction layer formed on the second electrode; wherein the negative friction layer comprises MXene and the positive friction layer comprises polyacrylonitrile (PAN) nanofibers.
[0017] Another objective of the present invention is to provide a method for manufacturing the triboelectric nanogenerator. means of solving the problem
[0018] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the present invention, and the present invention is defined only by the scope of the claims.
[0019] The terms used in this specification are for describing the embodiments and are not intended to limit the invention. In this specification, the singular form includes the plural form unless specifically stated otherwise in the text. The terms "comprises" and / or "comprising" used in this specification do not exclude the presence or addition of one or more other components in addition to the components mentioned. Throughout the specification, the same reference numerals refer to the same components, and "and / or" includes each of the mentioned components and all combinations of one or more. Although terms such as "first," "second," etc., are used to describe various components, these components are not limited by these terms. These terms are used merely to distinguish one component from another. Therefore, the first component mentioned below may be the second component within the technical scope of the invention.
[0020] Unless otherwise defined, all terms used herein (including technical and scientific terms) may be used in a meaning commonly understood by those skilled in the art to which the present invention pertains. Additionally, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless explicitly and specifically defined otherwise.
[0021] The present invention provides a triboelectric nanogenerator comprising: a first electrode formed on a first substrate; a second electrode formed on a second substrate and disposed opposite to the first electrode; a negative friction layer formed on the first electrode; and a positive friction layer formed on the second electrode; wherein the negative friction layer comprises MXene and the positive friction layer comprises polyacrylonitrile (PAN) nanofibers.
[0022] The MXene of the present invention can be added to a PVDF solution at various concentrations and electrospun to form PVDF@MXene.
[0023] The term PVDF@MXene in this invention refers to PVDF / MXene composite nanofibers and may be described interchangeably.
[0024] The above MXene may be characterized by being represented by the following chemical formula 1:
[0025] [Chemical Formula 1]
[0026] M n+1 X n Tx
[0027] In the above formula
[0028] M is a transition metal of group 3 to 7, and
[0029] X is C or N, and
[0030] Tx is -O, -F, or -OH, and n is an integer from 1 to 3.
[0031] The PAN nanofibers of the present invention can be decorated with a metal-organic framework (MOF).
[0032] The above MOF may include at least one of ZIF-90, ZIF-67, ZIF-8, ZIF-11, MIL-100(Cr), MIL-101(Cr), and MIL-100(Fe), and more specifically, may be ZIF-67.
[0033] The PAN nanofiber decorated with the above MOF forms a pearl necklace-shaped structure, and due to the structure, it can provide mechanical strength and flexibility.
[0034] The reaction time of the above PAN and MOF may be 1 to 24 hours, specifically 5 to 15 hours, and more specifically 10 hours.
[0035] In a specific embodiment of the present invention, it was confirmed that the surface roughness of the ZIF-67@PAN fiber (ZP-10h) produced by a 10-hour reaction had the highest value of 16.5 μm (Fig. 3 of the present invention).
[0036] The term ZIF-67@PAN in this invention refers to ZIF-67 / PAN composite nanofibers and may be described interchangeably.
[0037] The above MXene may be included in an amount of 1 to 15 weight% relative to the above PVDF@MXene, specifically in an amount of 7 to 10 weight%, and more specifically in an amount of 9 weight%.
[0038] In a specific embodiment of the present invention, when the MXene is included at 9 wt% based on PVDF@MXene, it was confirmed that the maximum dielectric constant value of 31.55 was reached (Fig. 13 of the present invention).
[0039] The triboelectric nanogenerator of the present invention has excellent electrical performance with a maximum output voltage of 300 V or more and a maximum output current of 10 μA or more.
[0040] In a specific embodiment of the present invention, it was confirmed that the triboelectric nanogenerator prepared with ZP-10h@PAN / PVDF@9wt%MXene of the present invention has excellent electrical characteristics of 305 V, 10.6 μA, and 98 nC (Fig. 6 of the present invention).
[0041] The above triboelectric nanogenerator operates in a vertical contact-separation mode and can generate current due to the potential difference between the positive friction layer and the negative friction layer.
[0042] In a specific embodiment of the present invention, the positive friction layer used ZIF-67@PAN nanofibers, and the negative friction layer used PVDF@MXene nanofiber flexible film.
[0043] The above triboelectric nanogenerator can convert AC power into DC power through a bridge rectifier and store energy in an external capacitor.
[0044] The energy stored in the above capacitor can be supplied as power to a small electronic device including an LED or a digital timer.
[0045] In a specific embodiment of the present invention, it was confirmed that the triboelectric nanogenerator of the present invention can store harvested energy in a capacitor by utilizing a bridge rectifier circuit and can be used to supply power to and drive an external electronic device (Fig. 7 of the present invention).
[0046] In addition, the present invention provides a method for manufacturing a triboelectric nanogenerator comprising the following steps.
[0047] A step of forming a first electrode formed on a first substrate;
[0048] A step of forming a second electrode formed on a second substrate and positioned opposite to the first electrode;
[0049] A step of forming a negative friction layer formed on the first electrode; and
[0050] The method includes the step of forming a friction layer of a certain amount formed on the second electrode;
[0051] The above negative friction layer includes MXene, and
[0052] A method for manufacturing a triboelectric nanogenerator, characterized in that the above-mentioned friction layer comprises polyacrylonitrile (PAN) nanofibers.
[0053] The negative friction layer of the present invention is characterized by using PVDF@MXene prepared by electrospinning by adding MXene to a PVDF solution.
[0054] The above MXene may be included in an amount of 1 to 15 weight% relative to the above PVDF@MXene, specifically in an amount of 7 to 10 weight%, and more specifically in an amount of 9 weight%.
[0055] The positive friction layer of the present invention is characterized by using MOF@PAN formed by electrospinning by immersing PAN in a MOF generating solution.
[0056] The reaction time of the above PAN and MOF may be 1 to 24 hours, specifically 5 to 15 hours, and more specifically 10 hours. Effects of the invention
[0057] The present invention provides a triboelectric nanogenerator and a method for manufacturing the same. More specifically, a triboelectric nanogenerator manufactured using ZIF-67@PAN as the positive friction layer and PVDF@MXene as the negative friction layer exhibits a charge of 305 V, 10.6 μA, 98 nC, and 10.9 W m² due to increased surface roughness and high charge induction resulting from contact electrification. -2 It has been confirmed that it has excellent electrical characteristics of power density, and it can be usefully used to power LEDs, power commercial capacitors, power LCDs of portable watches, and monitor human movement with self-driving sensors. Brief explanation of the drawing
[0058] Figure 1a is a diagram showing a schematic description of the synthesis procedure of electrospun ZIF-67@PAN fibers, and Figure 1b is a diagram showing a schematic description of the synthesis procedure of electrospun PVDF@MXene fibers. Figure 2a shows an FESEM image of ZIF-67 powder, Figure 2b shows an FESEM image of pure PAN fiber, Figure 2c shows an FESEM image of ZP-1h fiber film, Figure 2d shows an FESEM image of ZP-5h fiber film, Figure 2e shows an FESEM image of ZP-10h fiber film, Figure 2f shows an FESEM image of ZP-24h fiber film, Figure 2g shows the elemental mapping of ZP-10h film, and Figure 2h shows the EDX spectrum of ZP-10h film. Figure 3a shows the surface roughness profile (Ra) of ZIF-67 powder, Figure 3b shows the surface roughness profile (Ra) of PAN fiber, Figure 3c shows the surface roughness profile (Ra) of ZP-1h fiber film, Figure 3d shows the surface roughness profile (Ra) of ZP-5h fiber film, Figure 3e shows the surface roughness profile (Ra) of ZP-10h fiber film, and Figure 3f shows the surface roughness profile (Ra) of ZP-24h fiber film. Figure 4a shows a TEM image of pure PVDF, Figure 4b shows a TEM image of an MXene sheet, Figure 4c shows a TEM image of a PVDF@MXene (9 wt.%) composite taken at low magnification, Figure 4d shows a TEM image of a PVDF@MXene (9 wt.%) composite film, Figure 4e shows a TEM elemental mapping of a PVDF@MXene composite film, and Figure 4f shows an EDX spectrum of a PVDF@MXene composite film. Figure 5a is a figure showing the CS mode operation mechanism of the ZP-TENG device, Figure 5b is a figure showing the XRD profiles of pure PAN fiber, ZIF-67 powder, ZP-1h, ZP-5h, ZP-10h, and ZP-24h fiber films, Figure 5c is a figure showing the FTIR profiles of pure PAN fiber, ZIF-67 powder, ZP-1h, ZP-5h, ZP-10h, and ZP-24h fiber films, Figure 5d is a figure showing the XRD profiles of pure PVDF film and PVDF@MXene (9wt.%) composite fiber film, and Figure 5e is a figure showing the FTIR profiles of pure PVDF film and PVDF@MXene (9wt.%) composite fiber film. Figures 6a to 6l show the energy harvesting efficiency of the fabricated ZP-TENG device performed at 5 Hz and 4 N force. Fig. 7a shows the voltage performance of a ZP-TENG device optimized at 4 N and a frequency range of 1–5 Hz; Fig. 7b shows the current performance of a ZP-TENG device optimized at 4 N and a frequency range of 1–5 Hz; Fig. 7c shows the voltage and current of a ZP-TENG device optimized under various compression forces ranging from 1–15 N at a constant frequency of 5 Hz; Fig. 7d shows a ZP-TENG maintaining 10,000 cycle stability at 4 N and 5 Hz; Fig. 7e shows the voltage and current of a ZP-TENG device measured using various load resistances; Fig. 7f shows the power density of a ZP-TENG device measured using various load resistances; Fig. 7g shows the circuit diagram of a bridge rectifier used to power an LCD; Fig. 7h shows the TENG rectified voltage; and Fig. 7i shows various capacitors charged by the ZP-TENG Figure 7j shows the charge and discharge curves of a 10 μF capacitor, Figure 7k shows the display of an LCD timer clock being brightened using ZP-TENG, and Figure 7l shows the LED being turned on with the name "NBAL". FIG. 8 illustrates the installation of a ZP-TENG device at various locations on a smart door to establish self-actuated detection and practical applications, FIG. 8a illustrates the generation of electrical performance while opening the door, FIG. 8b illustrates the generation of electrical performance while tapping the door, FIG. 8c illustrates the generation of electrical performance while knocking the door, FIG. 8d illustrates the generation of electrical performance while tapping the foot, and FIG. 8e illustrates the generation of electrical performance while playing the bell "music icon" and "music off". Figure 9a shows a high-magnification FESEM image of ZIF-67 powder, Figure 9b shows a high-magnification FESEM image of pure PAN fiber, Figure 9c shows a high-magnification FESEM image of ZP-1h fiber film, Figure 9d shows a high-magnification FESEM image of ZP-5h fiber film, Figure 9e shows a high-magnification FESEM image of ZP-10h fiber film, and Figure 9f shows a high-magnification FESEM image of ZP-24h fiber film. FIGS. 10a to 10c show FESEM images of PAN nanofibers prepared under conditions of applied voltages of 10 kV, 15 kV, and 18 kV and a fixed rotation speed for the electrospinning process, FIGS. 10d to 10f show FESEM images of ZIF-67 grown on the PAN nanofibers, and FIGS. 10g and 10h show the electrical performance of a ZIF67@PAN / PVDF@MXene-based TENG device. Figures 11a and 11b show TEM images of ZIF-67@PAN nanofibers at 0.5 μm and 0.2 μm. Figure 12 is a figure showing the KPFM surface potential for PAN fibers, ZP-1h, ZP-5h, ZP-10h, and ZP-24h films. Figure 13 shows the dielectric constant analysis of pure PVDF fibers and PVDF fibers containing MXene, Figure 13a shows the dielectric constant measurements according to frequency, and Figure 13b shows the tangent loss measurements according to frequency. Figure 14 shows the charging performance of an optimized ZP-TENG device measured at various frequencies (1–5) and a constant force of 4 N. Figure 15a shows the voltage curves of a ZP-TENG subjected to compressive forces of 1, 2, 3, and 4 N at a fixed frequency of 5 Hz, and Figure 15b shows the current curves of a ZP-TENG subjected to compressive forces of 1, 2, 3, and 4 N at a fixed frequency of 5 Hz. Figure 16 is a figure showing the output power density of various TENG devices with various external load resistances. Figure 17 shows the mechanical properties of the ZP-10h film, Figure 17a shows the tensile stress-strain curve of the ZP-10h fiber film and the hysteresis loop (elongation rate: 0.5 mm / s) measured at various strains, and Figure 17b shows the stress-strain curve of the ZP-10h film cycle stability without resting periods between cycles. Figure 18 shows the actual application of dropping various weights onto the ZP-TENG device from a distance of 10 cm. Specific details for implementing the invention
[0059] The contents of the present invention will be explained in more detail below through the following examples and experimental examples. However, the scope of the present invention is not limited to the following examples and experimental examples, but includes variations of equivalent technical concepts.
[0060] Example 1. Preparation of materials
[0061] Cobalt (II) nitrate hexahydrate (Co(NO3)2ㆍ6H2O), 2-methylimidazole (2-MIM), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), N,N-dimethylformamide (DMF), methanol, lithium fluoride (LiF), acetone, and hydrochloric acid (HCl) were purchased from Sigma-Aldrich, South Korea.
[0062] The Ti AlC MAX phase precursor was purchased from Carbon-Ukraine Ltd., and the conductive adhesive aluminum foil, green LED, capacitor, and resistor were purchased from Device Mart, South Korea.
[0063] Example 2. Preparation of Electrospun PAN Nanofibers
[0064] Electrospun PAN nanofibers were prepared as follows. First, PAN was dissolved in DMF and stirred overnight to obtain a homogeneous solution, thereby preparing 13 wt% of the PAN solution. This solution was injected into a 10 mL syringe equipped with a 21G diameter needle. Aluminum foil wound around a rotating drum was used as a collector. The distance between the needle tip and the collector was fixed at 15 cm, the electrospinning voltage was 15 kV, and the solution flow rate was 1 mLh. -1 It was performed at.
[0065] Finally, the collected electrospun PAN nanofibers were dried in an oven at 70°C for 12 hours to remove residual DMF.
[0066] Example 3. Preparation of ZIF-67 powder
[0067] 1.3 g of Co(NO3)2·6H2O and 1.5 g of 2-MIM were each dissolved in 50 mL of methanol and stirred at 25 °C for 1 hour. The two solutions were combined and stirred at 25 °C for 10 hours. The resulting purple solution was centrifuged using deionized water and methanol, and the obtained solid was dried in a vacuum oven at 70 °C for 6 hours.
[0068] Example 4. Formation of a pearl necklace-like fiber film by coating PAN electrospun nanofibers with ZIF-67
[0069] Co(NO3)2·6H2O (1.24 g) was dissolved in 50 mL of methanol solution. Then, 0.02 g (3.5 × 3.5 cm) of the prepared electrospun PAN nanofiber was immersed in the solution and stirred for 30 minutes. Afterward, the PAN nanofiber was removed from the solution and rapidly washed with methanol and deionized water.
[0070] Separately, 1.5 g of 2-MIM was dissolved in 50 mL of methanol and stirred for 30 minutes. Then, the 2-MIM-methanol solution was slowly added to the Co(NO3)2·6H2O-methanol solution. Washed PAN fibers were immersed in the mixed solution while stirring for 1, 5, 10, and 24 hours to decorate the PAN nanofibers with ZIF-67 nanocrystals (ZIF-67@PAN). Then, after the specified time, the ZIF-67@PAN nanofibers were removed from the mixed solution, washed with deionized water, and dried overnight in a vacuum oven at 60 °C.
[0071] The pearl necklace-shaped ZIF-67@PAN nanofiber films obtained after immersion for various periods were labeled as follows. ZP-1 for the ZIF67@PAN-1h film, ZP-5h for the ZIF-67@PAN-5h film, ZP-10h for the ZIF-67@PAN-10h film, and ZP-24 for the ZIF-67@PAN-24h film.
[0072] Example 5. Ti 3 C 2 Synthesis of Tx MXene
[0073] MXene nanosheets (Ti3C2Tx) were prepared through an acid-based selective etching procedure and an exfoliation process. First, 1 g of lithium fluoride 9 M After adding to HCl, the mixture was mixed for 10 minutes using a magnetic stirrer. Subsequently, MAX phase (1 g) was added, and the mixture was stirred at 40 ℃ for 72 hours. The solution was centrifuged several times until the pH reached 7, and then freeze-dried to obtain several layers of MXene nanosheets.
[0074] Example 6. Preparation of PVDF nanofibers and PVDF / MXene nanofibers
[0075] Pure PVDF nanofibers and PVDF / MXene nanofibers were prepared by electrospinning. To synthesize PVDF nanofibers, a PVDF pellet (2.2 g) was dissolved in DMF (5 g) and acetone (4 g) and stirred thoroughly for 2 hours.
[0076] To synthesize PVDF / MXene nanofibers, MXene (3, 6, 9, or 11 wt%) was dissolved in a DMF solution and sonicated for 1 hour. PVDF (2.2 g) was added to the suspension and stirred at 100 °C for 2 hours, then acetone was added and stirred for 4 hours.
[0077] This rotary solution was poured into a 10 mL syringe equipped with a 21 G diameter needle. A rotary drum wrapped in aluminum foil was used as a collector, and spinning was performed with a distance of 18 cm between the collector and the tip. Electrospinning was performed at 15 KV, and the solution flow rate was 0.5 mLh -1 Finally, the collected nanofibers were dried in an oven for 12 hours to remove residual solvent.
[0078] Example 7. Fabrication of ZP-TENG device
[0079] The vertical contact-separation (CS) mode was used to design a TENG with an active area of 2.5 × 2.5 cm. Flexible ZIF-67@PAN nanofibers (thickness 370 μm) were used as the tribopositive layer, and a flexible PVDF@MXene nanofiber film was used as the tribonegative material.
[0080] The size of the ZIF-67@PAN nanofiber and PVDF@MXene film was 2.5 × 2.5 cm. Aluminum foil (2.5 x 2.5 cm), a conductive adhesive, was attached to the tribopositive and tribone layers, then a PP sheet was placed and covered with Kapton tape to support the triboelectric layer.
[0081] Example 8. Material Characterization and Electrical Measurement
[0082] The surface morphology of the tribofilm was investigated using FESEM (Hitachi S-4700, Japan). Elemental mapping analysis was performed via Oxford Instruments (UK), and HRTEM images were obtained using the JEM-2100F instrument.
[0083] Surface roughness was evaluated using a 2D optical surface profiler (Veeco Instrument Inc., Wyko NT1100, USA). Structural patterns were analyzed using a PANalytical X'Pert Pro multi-purpose X-ray diffractometer. FT-IR profiles were investigated using a Nicolet 6700 FT-IR spectrometer (Thermo Fisher Scientific).
[0084] An electrodynamic vibrator was used as a vibration source to generate uniform vertical contact separation, which was controlled using a function generator. The current and output voltage signals of the TENG device were evaluated using a digital phosphor oscilloscope (Tektronix DPO2022B) and a low-noise current preamplifier (model number SR570, Stanford Research Systems, Inc.).
[0085] Charge was measured using a Keithley 6514. KPFM surface potential was measured using a Park system (SR830, Stanford Research Systems) equipped with an AFM, XE-7, and a locking amplifier. Surface potential was detected using an AFM tip (NCST-Au). Permittivity analysis was performed using an LCR meter (4284 A, Hewlett-Packard). A general-purpose tensile analyzer (TXA analyzer, YEONJIN S-TECH) was used for tensile measurements.
[0086] Experimental Example 1. Synthesis and Characterization Analysis of ZIF-67@PAN Fibers and PVDF@MXene Fibers
[0087] Figure 1a schematically illustrates the synthesis process of ZIF-67 crystals (ZP) decorated on PAN nanofibers to form a fiber film resembling a pearl necklace. The surface morphological characteristics of PAN and ZIF-67 were investigated using FESEM. Figures 2 (low magnification) and 9 (high magnification) show the morphology and elemental mapping results of ZIF-67 powder, PAN fibers, ZIF-67@PAN fibers, and EDS.
[0088] Figures 2a and 9a show FESEM images of synthesized ZIF-67 nanocrystals, exhibiting randomly oriented, smooth, polyhedral or rhombohedral dodecahedral morphologies (size 400–500 nm). Figure 10 shows the effect of various electrospinning voltages (10, 15, and 18 kV) on the electrical behavior of TENG devices associated with fiber surface morphologies (original PAN and ZIF-67@PAN).
[0089] Figure 11 shows TEM images of ZIF-67@PAN nanofibers at 0.5 and 0.2 μm. The acquired TEM images show that ZIF-67 nanocrystals are distributed throughout the PAN nanofibers. Figures 2b and 9b show electrospun PAN fibers with an average diameter < 200 nm. Figures 2c to 2f and 9c to 9f show pearl necklace-shaped ZIF-67@PAN fiber films decorated by immersing them in a solution containing ZIF-67 nanocrystals for 1, 5, 10, or 24 hours. Figures 2e, 2f, 9e, and 9f show ZIF-67 nanocrystals attached to PAN nanofibers after immersion for 10 or 24 hours.
[0090] Figures 2g and 2h show the elemental mapping results of ZIF-67@PAN fibers soaked for 10 hours, confirming that Co, O, C, and N exist on the surface of the PAN fibers in a nanocrystalline form. EDS results displayed spectral lines for Co, C, O, and N, confirming the phase purity of ZIF-67@PAN (Figure 2h).
[0091] Figure 1b schematically illustrates the synthesis of PVDF nanofibers and PVDF / MXene nanofiber films. PVDF-MXene composite nanofiber films are formed through the synergistic blending of PVDF and MXene. Electrospinning involves stretching the PVDF solution into a uniaxial shape due to electrostatic repulsion under an applied electric field, which implies the conversion of the α-crystalline phase of PVDF into the β-crystalline phase. Additionally, incorporating MXene sheets into the PVDF solution results in electrostatic attraction between fluorine or hydrogen atoms and the functional groups of MXene.
[0092] The surface roughness of the material plays an important role in enhancing the electrical performance of the TENG. To verify this, the surface roughness of the fabricated materials was measured using a 2D optical surface profiler (Fig. 3). The average surface roughness (Ra) of ZIF-67 nanocrystals, PAN nanofibers, ZP-1h, ZP-10h, and ZP-24h was 0.88, 6.3, 10.5, 12.4, 16.5, and 16.3 μm, respectively.
[0093] As shown in Fig. 3, ZF-10 had a higher surface roughness than other manufactured materials. This means that a higher surface roughness can provide a larger surface area for contact electrification. The surface potential of the film plays an important role in achieving excellent electrical performance of the TENG device. Fig. 12 shows the KPFM surface potentials for pure PAN fiber (0.438V), ZP-1h (231.258V), ZP-5h (240.335V), ZP-10h (389.323V), and ZP-24h (319.007V) films.
[0094] The results obtained confirmed that pure PAN fibers and ZIF-67 grown on PAN fibers had positive surface potentials after different immersion times. Specifically, if there is a positive contact potential difference, electrons can easily pass through the surface. When the surface comes into contact with a PVDF@MXene layer, it easily becomes positively charged.
[0095] Figures 4a to 4c show the surface morphological profiles of pure PVDF nanofibers, MXene nanosheets, and prepared electrospun PVDF@MXene composite nanofibers. Figure 4a shows the fiber morphology of electrospun PVDF with an average fiber diameter of less than 200 nm. Figure 4b shows the sheet morphology of Ti3C2Tx MXene, and Figure 4c shows the fiber morphology of the PVDF@MXene (9 wt%) composite.
[0096] The diameter of the composite fibers falls within the range of 200 ± 100 nm. Figure 4d shows the morphology of the composite nanofibers confirmed via TEM, thereby confirming that MXene nanoparticles were inserted into the PVDF matrix. Figures 4e and 4f show the TEM elemental mapping images and EDAX spectra of the composite nanofibers, illustrating the confirmed predicted elemental distribution (C, F, Ti, and O elements) of the PVDF@MXene composite material.
[0097] Experimental Example 2. Analysis of the operating mechanism of the ZP-TENG device
[0098] The fabricated ZP-TENG device was operated in a vertical contact-separation mode, as schematically shown in Fig. 5a. To design the ZP-TENG device, ZIF-67@PAN nanofibers were attached to an Al electrode and used as the anode layer. PVDF@Ti3C2Tx MXene nanofibers on the Al electrode were used as the cathode layer.
[0099] Figure 5b schematically illustrates the proposed operating mechanism of the fabricated ZP-TENG device. The TENG basically operates based on the principles of electrostatic induction and contact electrification (coupling effect). Initially, no charge is generated in the ZP-TENG device. Furthermore, when the tribopositive layer (ZIF-67@PAN) and the tribonegative layer (PVDF@MXene) come into contact with each other, an opposite charge is generated in the triboelectric layer (Figure 5b panel i).
[0100] That is, a negative charge is generated in the PVDF@MXene layer and a positive charge is generated in the ZIF-67@PAN layer. Additionally, when the force is released, the device returns to the initial state, creating a potential difference between the electrodes. Consequently, due to the potential difference, electrons move between the upper and lower electrodes (Fig. 5b panel ii). Electron transfer continues until the two layers are completely separated (Fig. 5b panel iii).
[0101] The initial half-cycle of the electrical characteristics originates from this electron flow. However, when force is applied to the ZP-TENG device, the layers are pressed against each other and the electron flow occurs in the reverse direction (Fig. 5b panel iv). Electrons flow from the lower electrode to the upper electrode, creating another half-cycle of the electrical characteristics. Therefore, the electrical performance of the ZP-TENG device can be maintained through repeated contact and separation.
[0102] The crystallinity of ZIF-67 powder, PAN nanofiber film, ZP-1h film, ZP-5h film, ZP-10h film, and ZP-24h film was evaluated via XRD (Fig. 5b). The XRD of PAN showed a broad diffraction peak at approximately 17° corresponding to the (010) plane of PAN. Characteristic peaks of PAN (011), (002), (112), (222), and (134) were obtained in the 2θ range of 5°–60°.
[0103] No impurity peaks were observed, confirming the high quality and effective synthesis of ZIF-67 powder. Sharp diffraction peaks indicate the high crystallinity of ZIF-67. The XRD profiles of ZIF-67@PAN nanofiber films prepared using various immersion times matched the XRD patterns of PAN and ZIF-67, confirming that ZIF-67 nanoparticles were successfully formed on the surface of PAN fibers.
[0104] The peaks corresponding to the (011) and (112) planes increased as the immersion timing of the PAN nanofiber film in the ZIF-67 precursor increased. This indicates that the synthesis of ZIF-67@PAN fibers was successfully achieved with various applied times.
[0105] Fig. 5c is 4000-400 cm -1This shows the FT-IR spectra of ZIF-67 powder, PAN nanofiber film, ZP-1h film, ZP-5h film, ZP-10h film, and ZP-24h film recorded. The characteristic absorption peaks of pure PAN fiber are at 1075, 1242, 1360, 1454, 1738, 2242, and 2946 cm⁻¹. -1 It was observed in and was found to be due to C-O and CH vibrations, rocking vibrations of CH2, bending deformation of CH2, C〓O, C≡N, and stretching of CH2, respectively.
[0106] 1502~600cm -1 The characteristic peak of the range was assigned to the stretching and bending vibrations of the ZIF-67 imidazole ring. 1578 cm⁻¹ -1 The peaks were estimated to be attributed to C=C stretching mode vibrations. Additionally, at 1176, 1306, and 1420 cm -1 The peaks associated with the vibrations of the imidazole ring located at were estimated to be due to C-N stretching, C-H bending, and C-N stretching vibrations, respectively.
[0107] 755-465 cm -1 Distinct peaks in the range were assigned to coordination Co-N bonds at 2927 and 3128 cm⁻¹. -1 The characteristic peaks confirmed the presence of aromatic and aliphatic C-H stretching vibrational modes of 2-methylimidazole, respectively. All acquired vibrational and stretching modes confirmed the successful formation of the cobalt-imidazole complex in ZIF-67. The ZIF-67@PAN film exhibited a 2242 cm⁻¹, similar to that observed in PAN. -1 C≡N stretching vibrations were exhibited. Additionally, CH stretching and skeletal vibration peaks of the imidazole ring attributed to the ZIF-67 organic ligand were observed at 3136 and 1581 cm⁻¹, respectively. -1 It was discovered in.
[0108] The XRD analysis results for pure PVDF nanofibers and PVDF@MXene composite nanofibers with various MXene contents are shown in Fig. 5d. The distinct and strong (104) and (002) planes observed at 38.7° and 9.3° in all samples, respectively, were found to be due to MXene nanosheets.
[0109] As the MXene content increased, the diffraction peak of (002) increased, which is attributed to the intercalation of the PVDF chain and MXene layer assisted by functional groups on the MXene surface and fluorine and hydrogen atoms of the PVDF chain. In contrast, the β-peak (110 / 200 plane) became broader and was significantly suppressed as the MXene content increased. This indicates that as the MXene content increases, the β-crystallinity of the PVDF chain decreases.
[0110] Figure 5e shows the FTIR spectra of pure PVDF fibers and PVDF@MXene composite nanofibers with various MXene contents at 1404, 880, and 840 cm⁻¹. -1 While the peak is attributed to the β-phase, the 763 cm⁻¹ peak -1 The peak was found to be attributed to the α-phase. Increasing the MXene content in the PVDF matrix resulted in the 1190 and 840 cm⁻¹ peaks. -1 The absorption band intensity decreased, which was consistent with the XRD results.
[0111] The FTIR profile of the PVDF@MXene composite sample includes peaks similar to those of pure PVDF fibers, and the peak intensity was found to decrease slightly as the MXene concentration increased. This indicates an imbalance or difference in β-(TTT form) due to the reduction of C-F and C-H bonds, and a resulting decrease in nanofiber crystallinity. Through FESEM, XRD, and FTIR analysis, it was confirmed that PAN nanofibers were successfully decorated with ZIF-67 nanoparticles.
[0112] The electrical output performance of TENG devices is largely dependent on the transferred charge density, which in turn depends on the surface roughness, thickness, and dielectric properties of the triboelectric layer. The permittivity and triboelectric output of pure PVDF fibers incorporating MXene were evaluated. The dielectric behavior of PVDF@MXene nanofibers was investigated in detail using a complex permittivity model.
[0113] For analysis, Pi × (1 cm) 2 PVDF@MXene nanofiber films of a fixed size were used. The fixed-size PVDF@MXene nanofiber films were encapsulated between conductive adhesive aluminum tapes on both sides to form a parallel plate capacitor model. Figures 13a and 13b are 10 3 -10 6 Permittivity and dielectric loss are expressed as functions of frequency in the Hz frequency range.
[0114] An LCR meter was used to record the capacitance, phase, conductivity, and impedance of PVDF@MXene nanofiber films. Interfacial interactions between PVDF and MXene influence the formation of fine dipoles. As shown in Figure 13a, the dielectric constant values obtained by increasing the concentration of MXene (0, 3, 6, 9, 11 wt%) in PVDF nanofibers were 9.24–12.62, 20.54, 31.55, and 26.54, respectively. Figure 13a indicates that 9 wt% of MXene reached a maximum dielectric constant value of 31.55.
[0115] As the MXene concentration was further increased to 11 wt%, the dielectric constant value gradually decreased due to the penetration limit of the PVDF@MXene nanofibers. Similarly, the dielectric loss value varied as the MXene concentration relative to the PVDF nanofibers increased, as can be seen in Fig. 13b. In addition to the threshold fraction, the MXene components are coupled to enhance leakage current. This forms a conductive network within the PVDF matrix, which leads to a continuous increase in dielectric loss, as can be seen in Fig. 13b. The increase in dielectric loss does not benefit the dielectric constant of the material. The dielectric constant and dielectric loss obtain significant values at a 9 wt% MXene concentration. According to the dielectric analysis, the addition of MXene has the potential to improve the electron extraction capacity and dielectric constant of PVDF, thereby enhancing the triboelectric properties of the PVDF@MXene nanofibers.
[0116] Experimental Example 3. Evaluation of Energy Harvesting Efficiency of ZP-TENG Device
[0117] Figure 6 shows the energy harvesting efficiency of a ZP-TENG device (2.5×2.5 cm) fabricated at a constant operating frequency of 5 Hz with a force of 4 N. Figures 6a to 6c show the electrical behavior of a ZP-TENG device fabricated using ZIF-67 nanocrystal powder, and the electrical behavior of ZIF-67 decorated on PAN nanofibers as a positive tribolayer and on a clean PVDF nanofiber film as a negative tribolayer by immersing ZIF-67 for various times.
[0118] The device fabricated using a pure PVDF nanofiber film and ZP-10h exhibited the highest electrical performance (105 V, 2.3 μA, 35 nC), likely due to its higher surface roughness. On the other hand, the electrical characteristics of ZP-24h@PAN were slightly worse, with Ra values of 16.5 and 16.3 μm for ZP-10h@PAN and ZP-24h@PAN, respectively. Additionally, to improve output performance, various concentrations of MXene (3, 6, 9, 11 wt%) were added to PVDF (PVDF@MXene nanofiber film) and used as a negative tribolayer, while a pure PAN nanofiber film was used as a positive tribolayer.
[0119] As shown in Figs. 6d to 6f, PVDF containing 9 wt% MXene exhibited the best electrical performance (138 V, 2.56 μA, and 49.3 nC) at 5 Hz and 4 N due to better surface contact, PVDF intercalation of MXene, and roughness. Further experiments were performed using the optimized ZP-10h@PAN nanofiber film (positive tribo layer) and PVDF films containing various ratios of MXene (negative tribo layer) (Figs. 6g to 6i).
[0120] ZP-10h@PAN / PVDF@9 wt% MXene exhibited the best electrical properties (305 V, 10.6 μA, 98 nC). As the MXene concentration increases (i.e., 11 wt%), MXene nanosheets become more densely arranged within the PVDF matrix, reducing nanofiber film roughness and degrading electrical performance. Conversely, at low MXene nanosheet concentrations, the nanofibers are loosely embedded. Therefore, the competition between enhanced electrical properties and reduced roughness implies a decrease in TENG output at high concentrations of MXene nanosheets.
[0121] Finally, the electrical performance was investigated using an optimized PVDF@9wt.% MXene nanofiber film as the negative tribolayer and ZIF-67@PAN decorated with immersion for 1, 5, 10, or 24 hours as the positive tribolayer (Figs. 6j to 6l). The electrical performance of the PAN film was found to increase with immersion time. The ZP-TENG device fabricated with PVDF@9wt.% MXene and ZIF-67-10h@PAN achieved the best electrical performance (305 V, 10.6 μA, and 98 nC).
[0122] ZP-10h@PAN and ZP-24h@PAN exhibited nearly similar electrical behavior, with ZP-10h showing slightly higher electrical behavior. This is consistent with surface roughness analysis, where Ra of ZP-10h@PAN is 16.5 μm and Ra of ZP-24h@PAN is 16.3 μm. The notable electrical performance results can be attributed to the tribopositive properties of the ZIF-67@PAN nanofiber film, the surface roughness of PAN, the presence of MXene in the PVDF film, the good contact surface, and the intercalation of MXene by PVDF.
[0123] Figures 6j to 6l confirmed that the ZP-TENG device fabricated with PVDF@9wt.% MXene and ZIF-67-10h@PAN film achieved the best electrical performance. To gain a deeper understanding of the fabricated ZP-TENG device and its usability in various scenarios, it is necessary to investigate the performance of the device at various contact frequencies and constant forces.
[0124] The electrical output performance of the optimized ZP-TENG device was evaluated at various frequencies and a constant force of 4 N (Figs. 7a, 7b, and S6). The device harvested a corresponding electric voltage at a constant compressive force of 4 N. As the frequency was increased from 1 Hz to 5 Hz, the voltage, current, and charge increased. The results obtained indicate that frequency plays a widespread and key role in the output frictional operation of the ZP-TENG.
[0125] In general, various levels of force shock can be applied to the TENG device in everyday environments. Therefore, it is necessary to study the effect of force on the TENG electrical output (voltage and current). Figure 7c shows the voltage and current of a ZP-TENG device exposed to various compressive forces (1–15 N) at a constant frequency (5 Hz). Figures 15a and 15b show the voltage and current curves of the ZP-TENG when subjected to compressive forces of 1, 2, 3, and 4 N at 5 Hz.
[0126] According to the obtained electrical results, the voltage and current of the ZP-TENG device gradually increase from 91.0 V and 2.45 μA to 430.6 V and 22.75 μA as the external pushing force increases from 1 N to 15 N. This increase in electrical output characteristics is due to the fact that the interatomic distance between the cathode and anode tribolayers of the ZP-TENG device shortens and the electron clouds overlap more due to various external forces.
[0127] As shown in Fig. 7d, the energy generation efficiency of the ZP-TENG remained stable without a significant drop in output voltage after cycling (Fig. 7d). It demonstrated impressive long-term stability, as no degradation of the triboelectric pair was observed even after 1,000 cycles at 5 Hz with a load of 4 N. In addition, 10 2 ~10 9The dependence of the electrical output behavior on various external load resistances in the Ω range was also investigated (Fig. 7e). The results show that as the load resistance increases, the voltage increases, and the current decreases due to resistance losses.
[0128]
[0129] Here, R L represents the external load resistance, and A is the area of the TENG device (2.5 × 2.5 cm²) 2 ) and I represents the output current. As shown in Fig. 7f, the power density initially showed an increasing trend as the load resistance increased, then gradually decreased. Specifically, the maximum power density value is the external load resistance is When it is 40 mΩ 10.9 W m -2 The achieved power density is sufficient to power portable and wearable electronic devices.
[0130] Further comparative peak power density analysis was performed on TENG devices fabricated using pure PVDF / ZP-10h, pure PAN / PVDF@MXene (9 wt.%), and ZP-10h / PVDF@MXene 9 wt.% by applying different external load resistances (Fig. 16). As shown in Fig. 16, when a 40 mΩ load resistance is connected to ZP-10h / PVDF@MXene 9 wt.%, the maximum power density is approximately 10.91 W m⁻² -2 This is superior to other TENG devices. To accurately represent the performance level of the TENG of the present invention, Table 1 below compares the electrical behavior of the ZP-TENG fabricated according to the present invention. It is noteworthy that the fabricated ZP-TENG device exhibited the highest TENG electrical performance compared to reported ZIF-based TENGs.
[0131] [Table 1]
[0132]
[0133] It is essential to integrate energy harvesting devices with energy storage devices. In this regard, the design of a TENG-based self-generating charging system is required. By utilizing a bridge rectifier circuit, energy harvested from the TENG can be stored in a capacitor and later used to power and drive external electronic devices. A schematic diagram of the bridge rectifier used is shown in Fig. 7g. The fabricated ZP-TENG device was also used to power portable electronic devices such as LEDs and LCDs in portable watches.
[0134] To power the capacitor, the output of the ZP-TENG was converted from AC to DC through a bridge rectifier circuit and then connected to the capacitor. The rectified voltage is stored in the capacitor before connecting the LCD of the handheld watch. Fig. 7h shows the rectified voltage (305 V) harvested by the fabricated ZP-TENG at 4 N, 5 Hz. The rectified voltage was collected for approximately 300 seconds using 2.2, 4.7, 10, 22, 47, and 100 μF capacitors, and accumulated maximum voltages of 15, 8, 4.2, 1.8, 1.1, and 0.5 V were obtained, respectively (Fig. 7i).
[0135] The stored electrical energy was used to power a digital timer clock for more than 5 seconds (Fig. 7k). The ZP-TENG was also used to power 40 green LEDs named "NBAL" by tapping them gently with a hand (Fig. 7l). This demonstrates the potential benefits of the fabricated ZP-TENG device as a self-powered power supply system.
[0136] In addition, the mechanical properties of the optimized ZP-10h film were evaluated as shown in Fig. 17. The recovery of deformation of the ZP-10h fiber film was studied through cyclic tensile tests. The ZP-10h fiber specimens were extended at strains ranging from 10% to 50% at room temperature, and the tensile speed was v = 0.5 mm s⁻¹-1 The elongation / release cycle exhibited strain recovery for a maximum strain of 50% (Fig. 17a). The hysteresis between the elongation and release stress-strain curves is shown in Fig. 9a.
[0137] The ZP-10h fiber sample underwent 10 consecutive loading-unloading cycles without rest time between cycles. This indicates the stability of the ZP-10h film (Fig. 17b). When subjected to various mechanical kinetic stimuli, the TENG generates electrical energy. Furthermore, with energy harvesting capabilities, the TENG has significant potential as a self-driven sensing tool. The ZP-TENG was used to generate electricity from everyday human activities.
[0138] Experimental Example 4. Application of the ZP-TENG device
[0139] As shown in Fig. 8, the TENG device was mounted at various locations on the smart door to generate electrical energy during door opening, tapping, knocking, and leg tapping. Additionally, the ZP-TENG device was also used to harvest energy while ringing a bell. More specifically, when the device was placed on the door handle and subjected to external compressive force, the ZP-TENG device generated an average voltage of 28 V (Fig. 8a).
[0140] When the device is mounted in the center of a door and tapped, an average voltage of 35 V is generated (Fig. 8b). When mounted on a door and tapped by hand under this stimulus, the ZP-TENG device generates an average voltage of 18 V (Fig. 8c). When placed on the floor and stepped on, an average voltage of 3 V was generated (Fig. 8d). In addition, when placed in a position where a bell music is played on a speaker, an average voltage of 0.4 V was generated (Fig. 8e). Furthermore, it was confirmed that the ZP-TENG device can be used as a weight sensor.
[0141] After placing the ZP-TENG device on the floor, electrical performance was evaluated by dropping small objects of various weights from a height of 10 cm. Objects weighing 4.6 g, 10.1 g, 15.4 g, and 39.1 g generated voltages of 2.5 V, 5.2 V, 9.8 V, and 25 V, respectively (Fig. 18). These results demonstrate that the fabricated ZP-TENG device can be utilized in offices or smart homes to generate electricity from discarded mechanical motion and power portable electronic devices and self-driving sensors.
[0142] In summary, first, PAN nanofibers with rough surface roughness were produced. These nanofibers were decorated with ZIF-67 nanocrystals to form fibers resembling a pearl necklace. The immersion time of the PAN fibers in the ZIF-67 solution played a crucial role in decorating the PAN fiber films with ZIF-67 nanocrystals. The produced ZIF-67@PAN nanofibers provided an improved and efficient surface contact area, promoting charge generation and offering higher roughness. PVDF@MXene nanofiber films were prepared with varying amounts of MXene.
[0143] Integrating MXene into electrospun PVDF improves the charge transport and dielectric properties of ZP-TENG devices. ZIF-67@PAN is used as a positive triboelectric layer, and PVDF@MXene is used as a negative triboelectric layer. PVDF and PAN possess abundant polar C≡N and fluorine groups, which enhance triboelectricity and lay the foundation for high TENG output.
[0144] The optimized ZP-10h@PAN / PVDF@9wt.% MXene film exhibited high electrical performance due to a significant increase in the surface roughness of the ZIF-67@PAN fiber film and high charge induction resulting from contact electrification. The ZP-TENG device operated at 305 V, 10.6 μA, a charge of 98 nC, and 10.9 W m -2It exhibited excellent electrical characteristics, such as power density.
[0145] The fabricated ZP-TENG device was used to power 40 LEDs arranged in “NBAL” with a simple hand tapping motion, to power a fast-charging commercial capacitor, to power the LCD of a portable watch, and to monitor human movement with a self-driving sensor. The present invention developed a strategy to create and improve roughness using ZIF material on a polymer fiber film.
[0146] Although embodiments of the present invention have been described above, the present invention is not limited to the above embodiments and can be manufactured in various different forms, and those skilled in the art will understand that the present invention can be implemented in other specific forms without changing the technical concept or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive.
Claims
Claim 1 A triboelectric nanogenerator comprising: a first electrode formed on a first substrate; a second electrode formed on a second substrate and disposed opposite to the first electrode; a negative friction layer formed on the first electrode; and a positive friction layer formed on the second electrode; wherein the negative friction layer comprises PVDF nanofibers containing MXene, and the positive friction layer comprises polyacrylonitrile (PAN) nanofibers decorated with ZIF-67, and the PAN nanofibers decorated with ZIF-67 are nanofibers prepared by a 10-hour reaction of PAN and ZIF-67, and are characterized by having a structure in the shape of a pearl necklace. Claim 2 delete Claim 3 Triboelectric nanogenerator according to claim 1, characterized in that the MXene is represented by the following chemical formula 1: [Chemical Formula 1]M n+1 X n In the above formula, M is a transition metal of group 3 to 7, X is C or N, Tx is -O, -F or -OH, and n is an integer from 1 to 3. Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 A triboelectric nanogenerator according to claim 1, characterized in that the triboelectric nanogenerator has a maximum output voltage of 300 V or more and a maximum output current of 10 μA or more. Claim 8 A triboelectric nanogenerator according to claim 1, characterized in that the triboelectric nanogenerator operates in a vertical contact-separation mode to generate current by the potential difference between the positive friction layer and the negative friction layer. Claim 9 A triboelectric nanogenerator according to claim 1, characterized in that the triboelectric nanogenerator converts alternating current power into direct current through a bridge rectifier and stores energy in an external capacitor. Claim 10 A triboelectric nanogenerator according to claim 9, characterized in that the triboelectric nanogenerator supplies power to a small electronic device including an LED or a digital timer, using energy stored in the capacitor. Claim 11 A method for manufacturing a triboelectric nanogenerator comprising: a step of forming a first electrode formed on a first substrate; a step of forming a second electrode formed on a second substrate and disposed opposite to the first electrode; a step of forming a negative friction layer formed on the first electrode; and a step of forming a positive friction layer formed on the second electrode; wherein the negative friction layer comprises PVDF nanofibers containing MXene, and the positive friction layer comprises polyacrylonitrile (PAN) nanofibers decorated with ZIF-67, and the PAN nanofibers decorated with ZIF-67 are nanofibers prepared by a 10-hour reaction of PAN and ZIF-67, and are characterized by having a structure in the shape of a pearl necklace. Claim 12 A method for manufacturing a triboelectric nanogenerator according to claim 11, wherein the negative friction layer is characterized by using a PVDF / MXene composite nanofiber prepared by electrospinning by adding MXene to a PVDF solution. Claim 13 A method for manufacturing a triboelectric nanogenerator according to claim 12, characterized in that the MXene is included in an amount of 1 to 15 weight% relative to the PVDF / MXene composite nanofiber. Claim 14 A method for manufacturing a triboelectric nanogenerator according to claim 11, characterized in that the friction layer of the above amount uses a MOF / PAN composite nanofiber formed by electrospinning by immersing PAN in a MOF generating solution. Claim 15 delete
Citation Information
Patent Citations
Triboelectric nanogenerator and the manufacturing method thereof
KR1020190084555A
Composite, preparation method thereof, and personal thermal management device comprising same
KR1020220144674A
Triboelectric Nanogenerator with Staggered Electrodes
KR1020230061199A
Triboelectric generator-supercapacitor integrated device and manufacturing method thererof
KR1020230122771A
Apparatus for generating triboelectricity and method for manufacturing the apparatus
KR1020210011241A
